EFFECT OF YOGA ON EXAMINATION ANXIETY: A SYSTEMATIC REVIEW - Abbasi, Nargis; Ghosh, Shilpi (International Journal of Psychosocial Rehabilitation, 2020)
Examination anxiety is a prevalent problem for many students. It is a type of performance anxiety. Examination anxiety may affect 10-40 percent of all students. Yoga has been practiced over 3000 years. It is a bodymind intervention having healing effect. Recent empirical studies have revealed that a regular practice of yoga and meditation is very effective in decreasing the levels of different types of anxiety. As examination anxiety is a sub-type of anxiety, so the purpose of this investigation is to conduct a fully comprehensive review of literature related to the effect of yoga on reducing symptoms of examination anxiety as well as overall anxiety. This review study focused on total 25 number of published studies where participants suffered from anxiety. The studies ensure that yoga may be considered as an alternative or supportive technique to the pharmacological therapy. The review supported the positive effect of yoga on examination anxiety as well as on overall anxiety.